Influence of therapy on risk of cancer in rheumatoid arthritis. Pathophysiological principles - Waldner, Maximilian; Strangfeld, A.; Aringer, Martin (Zeitschrift für Rheumatologie, 2016)
The increased incidence of certain tumor entities in chronic inflammation and infections as well as the increased tumor risk under immunosuppression, illustrate the multiple and complex influences of the immune system on tumor pathogenesis. It is therefore conceivable that immunomodulatory therapy for rheumatoid arthritis (RA) could also influence the risk of malignancies, apart from treating the underlying disease. Basic scientific research studies have identified various signal transduction pathways that are relevant for tumorigenesis and tumor defense mechanisms. This review presents the current knowledge on the effects of the immune system on the occurrence of cancer and tries, where possible, to relate it to specific treatment options.
EVALuna2:2110